2020
DOI: 10.2147/jpr.s263315
|View full text |Cite
|
Sign up to set email alerts
|

<p>Preoperative Administration of Extended-Release Dinalbuphine Sebacate Compares with Morphine for Post-Laparoscopic Cholecystectomy Pain Management: A Randomized Study</p>

Abstract: Purpose Perioperative pain management plays a critical role in the effort to promote enhanced recovery after surgery (ERAS). Pain is also the most concern for patients after laparoscopic cholecystectomy (LC). Naldebain (extended-release dinalbuphine sebacate, DS) is an oil-based formulation for intramuscular injection that has been designed for extended release and can be used for preoperative analgesia over a 7-day period. This study was aimed to compare the efficacy of DS injection with that of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…It has shown benefits of less postoperative analgesic consumption and sufficient efficacy in POP pain intensity management. 12 , 16 , 17 …”
Section: Introductionmentioning
confidence: 99%
“…It has shown benefits of less postoperative analgesic consumption and sufficient efficacy in POP pain intensity management. 12 , 16 , 17 …”
Section: Introductionmentioning
confidence: 99%
“…DS (Naldebain ® Injection, Lumosa Therapeutics, Taiwan) was introduced in Taiwan in 2017; it, via intramuscular injection, delivers and maintains an effective nalbuphine analgesic blood level for approximately 7 days (Huang et al, 2020). Our previous study showed DS provided satisfying postoperative pain relief for laparoscopic cholecystectomy (Lee et al, 2020). The postoperative pain scores of laparoscopic bariatric surgery are variable from 6 to 8 out of 10 ( Gerbershagen et al, 2013;Brummett et al, 2017).…”
Section: Discussionmentioning
confidence: 97%
“…DS is an extended-release prodrug of nalbuphine which acts as a partial agonist at the κ-opioid receptor and a weak antagonist at the µ-opioid receptor; it is slightly less potent than morphine. Compared to morphine, DS produces less dependence, less sedation, and less respiratory depression (Yeh et al, 2017;Lee et al, 2020). DS (Naldebain ® Injection, Lumosa Therapeutics, Taiwan) was introduced in Taiwan in 2017; it, via intramuscular injection, delivers and maintains an effective nalbuphine analgesic blood level for approximately 7 days (Huang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a previous phase III study in a population undergoing haemorrhoidectomy demonstrated that the analgesic effect of DS was capable of lasting for about 6 days [12]. The safety and efficacy of DS were also investigated with regard to post-operative pain control of several types of abdominal surgery [13][14][15].…”
Section: Introductionmentioning
confidence: 99%